2014
DOI: 10.1139/cjpp-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epigallocatechin gallate on hepatocytes isolated from normal and partially hepatectomized rats

Abstract: Epigallocatechin gallate (EGCG) is an antioxidant found in green tea. In this study, male Wistar rats were subjected either to partial hepatectomy (PHx), or a sham operation (LAP). Twenty-four hours after surgery, hepatocytes were isolated and treated with various concentrations of EGCG for up to 72 h. We then measured markers of cell viability, oxidative stress, DNA synthesis, and caspase activity. Morphological criteria, cell viability tests, and albumin synthesis revealed toxicity starting at 10 μmol/L. DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Our observations of proapoptotic action of EGCG are in accord with our previous study [ 59 ] as well as with findings of other authors [ 11 , 52 , 67 ] but at variance with some others [ 49 ]. In our experiment, EGCG-induced apoptosis was proved by caspase 3 activity, DAPI staining, and oligonucleosomal DNA fragmentation (data not shown).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our observations of proapoptotic action of EGCG are in accord with our previous study [ 59 ] as well as with findings of other authors [ 11 , 52 , 67 ] but at variance with some others [ 49 ]. In our experiment, EGCG-induced apoptosis was proved by caspase 3 activity, DAPI staining, and oligonucleosomal DNA fragmentation (data not shown).…”
Section: Discussionsupporting
confidence: 94%
“…It was suggested that green tea extract may be less toxic due to the presence of other compounds, such as vitamin C [ 46 ]. On the other hand, the toxic concentration found in the present study is the same as in our previous study in hepatocytes isolated from rats after partial hepatectomy or laparotomy [ 59 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, high doses of EGCG were found to be hepatotoxic [8, 1113]. Similarly, EGCG displayed toxicity on mitochondria in permeabilized hepatocytes [8] and on mitochondria in a hepatoma cell line [14].…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, there are numerous benefits in using EGCG in the diet of a healthy individual and biochemically, and, specifically, cytologically effects have been studied in detail. Cytoprotective effects ascribed to this compound have been identified in the liver, kidney, heart, and lungs (Mezera et al, 2014;Kucera et al, 2015). Nuclear factor erythroid 2 -related factor 2 (NRF2) is a key regulator of the cellular antioxidant response.…”
Section: Green Tea Polyphenols (Gtps)mentioning
confidence: 99%